Kebijakan Pembangunan Nasional: dari Pertumbuhan (Growth) Menuju Kebahagiaan (Happiness) - Wibowo, Muhammad Ghafur (UIN Sunan Kalijaga, 2016)
This study aims to demonstrate the reorientation toward the national development policy of quantitative macro size (growth) towards a more qualitative measure (happiness). The test results of multiple linear regression on the variable value of public happiness index in each province of Indonesia with variable poverty, income inequality and income per capita shows quite interesting results. Apparently, only the poverty variable has significant negative effect on the happiness index. This means that poor people in Indonesia who have limitations in various aspects of life feel the lowest levels of happiness. Another interesting finding is that income and the income gap does not significantly influence the level of happiness of society. Therefore, the government needs to pay more attention to various aspects such as the quality of family life, social and various other aspects.